Peningkatan Pengetahuan Petani melalui Penyuluhan Pascapanen Cabai pada Kelompok Tani Kebun Berseri, Bintaro, Jakarta Selatan - Dahlia Nauly; Helfi Gustia; Rosdiana Rosdiana; Siska Yuningsih; Hafiz Dwiputro (Institut Pertanian Bogor, 2022)
Chili is a perishable product which require farmers to maintain its freshness. Rotten chili can not be sold causing the profits to decrease. One way to minimize the damage level of post harvest agricultural products is by applying the Good Handling Practice (GHP) system. The application of GHP will reduce the risk of contamination of fresh chili during handling, packaging, storage and transportation. The objective of this activity is to increase Kebun Berseri farmer’s group knowledge, ability and skill in handling chili post harvest and processing activities. The method of implementing this activity was extension, demonstration and evaluation. Extension activity was conducted using lecturing method. The topic discussed was related to increasing the value added, processing techniques for commercially valuable chilies, packaging techniques and a broader marketing system. Demonstrations were conducted to improve the skills of farmer’s group members in applying Good Handling Practice (GHP) correctly. The results of the evaluation showed that from these activities, farmers gained additional knowledge and new technology related to post-harvest handling and processing of chilies into shredded and chili oil.